Effects of Corporate Governance Disclosure on Profitability of Public Listed Firms in Tanzania - Beny Mwenda; Magwana Ngollo (Ilomata International Journal of Tax and Accounting, 2022)
This study investigated the effect of corporate governance information (CGI) disclosure on profitability of firms listed in the Dar es Salaam Stock Exchange (DSE). 21 listed companies were studied for a period ranging from 2006 to 2021 using a mixed research method with an explanatory sequential design. Return on equity (ROE) and Return on Assets (ROA) were employed as dependent variables in the panel data analysis. CGI disclosure was an independent variable. Geographical diversification, firm age, firm size, and sales growth were the control variables. Secondary data was obtained from DSE. Qualitative data was gathered via semi-structured interviews. Thematic analysis and a random effect model with two estimates (1 and 2) were utilized to analyze qualitative and quantitative data respectively. The findings suggested that there was a positive and significant effect of CGI disclosure on firm profitability. The findings adds to the body of knowledge by signifying stakeholder’s theory. The study concluded that Disclosure of CGI may undeniably result in increased profitability. We recommended that firm managers should pay a closer look at CGI disclosure, enhance their disclosure practices, and invest in disclosure strategies that will benefit stakeholders.